Childhood trauma in obese and overweight women with food addiction and clinical-level of binge eating. (August 2016) - Imperatori, Claudio; Innamorati, Marco; Lamis, Dorian A.; Farina, Benedetto; Pompili, Maurizio; Contardi, Anna; Fabbricatore, Mariantonietta
Abstract: Childhood trauma (CT) is considered a major risk factor for several disorders as well as for the development of eating psychopathology and adult obesity. The main aims of the present study were to assess in overweight and obese women: (i) the independent association between CT and food addiction (FA), and (ii) CT in patients with both FA and clinical-level of binge eating (BE), versus patients who only engage in FA or BE. Participants were 301 overweight and obese women seeking low-energy-diet therapy. All of the patients were administered self-report measures investigating FA, BE, CT, anxiety and depressive symptoms. CT severity was moderately and positively associated with both FA ( r = 0.37; p < 0.001) and BE ( r = 0.36; p < 0.001) severity. The association between FA and CT remained significant after controlling for potential confounding variables. Furthermore, compared to patients without dysfunctional eating patterns, the co-occurrence of FA and BE was associated with more severe CT as well as with more severe psychopathology (i.e., anxiety and depressive symptoms) and higher BMI. Our results suggest that clinicians should carefully assess the presence of CT in individuals who report dysfunctional eating patterns in order to develop treatment approaches specifically for obese and overweight patients with a history of CT.